A Comparative Technoeconomic Analysis of Algal Thermochemical Conversion Technologies for Diluent Production. Issue 11 (17th October 2019) - Kumar, Mayank; Oyedun, Adetoyese Olajire; Kumar, Amit
Abstract : Microalgae offer desirable attributes as a renewable feedstock. Herein, a technoeconomic assessment of using microalgae to produce chemicals (diluent) for bitumen transport is conducted. Two thermochemical technologies, hydrothermal liquefaction (HTL) and fast pyrolysis, are analyzed for a plant of 2000 dry t day −1 . A detailed process model is developed for the two thermochemical conversion technologies and used to perform a data‐intensive technoeconomic assessment to estimate diluent cost using biomass. The product values of diluents from HTL and pyrolysis are 1.60 ± 0.09 and 1.69 ± 0.11 $ L −1, respectively. The sensitivity analysis indicates that product yield has the highest impact on product value, followed by the biomass cost. The effect of using industrial carbon dioxide in a situation where the producer pays to the algae conversion plant to avoid paying a carbon levy is assessed. For HTL and fast pyrolysis, diluent cost falls to 1.06 and 1.16 $ L −1, respectively, when carbon tax increases to 40 $ t −1 . Herein, insights into the technoeconomic feasibility of producing chemicals from algal‐based thermochemical technologies are offered. Abstract : The growing interest in algae in the scientific and academic communities suggests the feasibility of producing various desired products from microalgae. The approach herein is to improve the sustainability of oil sands operations through the development of novel pathways of diluent production through thermochemical conversion methods, hydrothermal liquefaction (HTL), and fast pyrolysis.